Designing an Excellence Pattern for Effective Human Resources in the Oil Industry - ZAHIRI, ALI; BEHESHTIFAR, MALIKEH; POURKIANI, MASOUD; SHEIKHI, AYYUB (The journal of contemporary issues in business and government, 2021)
The purpose of this study was to design an effective human resource excellence model in the oil industry. The statistical population of the study consisted of two groups: the first group consisted of experts familiar with human resources management and the second group included experts in the field of Iranian oil industry. The research method was descriptive-survey. Data collection was done using Human Resources Excellence Questionnaire and Organizational Effectiveness. Data were analyzed by SPSS version 21, 17.8.8, MINITAB and LISREL. The results indicate that there is a meaningful relationship between the strategies and dimensions of human resources with the components of effectiveness in the oil industry. There is a meaningful relationship between the processes and its dimensions with the components of effectiveness in the oil industry. There is a meaningful relationship between the empowerment and its dimensions with the components of effectiveness in the oil industry.